The retinoid‐related orphan receptor alpha is essential for the end‐stage effector phase of experimental epidermolysis bullosa acquisita. Issue 1 (15th June 2015) - Sadeghi, Hengameh; Gupta, Yask; Möller, Steffen; Samavedam, Unni K; Behnen, Martina; Kasprick, Anika; Bieber, Katja; Müller, Susen; Kalies, Kathrin; de Castro Marques, Andreia; Recke, Andreas; Schmidt, Enno; et al.
Abstract Genetic studies have added to the understanding of complex diseases. Here, we used a combined genetic approach for risk‐loci identification in a prototypic, organ‐specific, autoimmune disease, namely experimental epidermolysis bullosa acquisita (EBA), in which autoantibodies to type VII collagen (COL7) and neutrophil activation cause mucocutaneous blisters. Anti‐COL7 IgG induced moderate blistering in most inbred mouse strains, while some showed severe disease or were completely protected. Using publicly available genotyping data, we identified haplotype blocks that control blistering and confirmed two haplotype blocks in outbred mice. To identify the blistering‐associated genes, haplotype blocks encoding genes that are differentially expressed in EBA‐affected skin were considered. This procedure identified nine genes, including retinoid‐related orphan receptor alpha (RORα), known to be involved in neurological development and function. After anti‐COL7 IgG injection, RORα+/− mice showed reduced blistering and homozygous mice were completely resistant to EBA induction. Furthermore, pharmacological RORα inhibition dose‐dependently blocked reactive oxygen species (ROS) release from activated neutrophils but did not affect migration or phagocytosis. Thus, forward genomics combined with multiple validation steps identifies RORα to be essential to drive inflammation in experimental EBA. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.